The Impact of ADHD on Employment and Work - Sadik, Hanan (2023)
The purpose of this research was to study the impact of ADHD on employment and work. The research aimed at studying the path connecting ADHD and its impact on work and employment. Therefore, the research used construct variables to measure the impact of ADHD on employment and work. The construct variables were work engagement, task performance, and counterproductive work behavior. The research used 30 respondents all of who suffered from ADHD and were in employment. This study utilized a descriptive research design which facilitated the discussion of the relationship between variables. The results indicated that ADHD had a negative impact on work engagement and task performance. There was positive correlation between ADHD and counterproductive behaviors. ADHD enhanced the rate of counterproductive work behaviors in employment and work. The use of these construct variables indicated the strong impact ADHD had on employment and work.